Study and evaluation of antimicrobial activity and antioxidant capacity of dry extract and fractions of leaves of Raphanus sativus var. oleiferus Metzg. (Bioscience Journal, 2020)
The radish (Raphanus sativus L.) is a vegetable of the Brassicaceae family cultivated worldwide and has several medicinal properties. Its biological activities are related to various secondary metabolites present in the species, especially phenolics. Thus, the objectives of this study were the chemical analysis and evaluation of the antioxidant and antimicrobial activities of the dry extract and fractions of the fodder turnip leaves (R. sativus var. oleiferus Metzg.). Samples were analyzed by mass spectrometry and the antioxidant activity was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical method and the reducing power method. Antimicrobial activity was determined by the agar diffusion and microdilution methods. The total phenols were concentrated in the butanol fraction (121.27 mg GAE/g) and the flavonoids were concentrated in the ethyl acetate fraction (98.02 mg EQ/g). The ethyl acetate fraction showed the best antioxidants results, with 83.45% of free radical scavenging and 11.34% of ferric ions reduction. The analysis of antimicrobial activity showed that the dry extract had the highest average zone of inhibition against Bacillus subtilis (18.67 mm). Smaller values of the minimum inhibitory concentration for Micrococcus luteus were, and the ethyl acetate fraction showed a lower minimum inhibitory concentration (0.1 mg/ml) for that microorganism. There was a strong correlation between the antioxidant activity and the content of phenols and flavonoids. The results showed the potential antioxidant and antimicrobial activities of this extract with the ethyl acetate fraction being most promising for further studies.